The Link between Specific Learning Difficulties and Behavioral Problems in primary school - Δανοπούλου Ελβίρα-Ελένη; Πίττα Ευδοκία (Education Sciences, 2020)
The aim of this cross-sectional study was to investigate whether primary school students with Specific Learning Difficulties, aged 6 – 12, displayed behavioral problems and whether gender is associated with behavioral problems. The clinical group consisted of 100 students with Specific Learning Difficulties and the control group consisted of 100 typically developed students. Teachers provided information on behavior through the Achenbach questionnaires Teacher’s Report Form. Teachers reported that the clinical group displayed significantly more Anxious/Depressed, Withdrawn/Depressed, Social Problems, Attention Problems and mostly Inattention and Aggressive Behavior than the control group. Students with dyslexia displayed less Somatic Complains, Social Problems, Rule- Breaking Behavior, Aggressive Behavior, Attention Problems and Inattention than the students with dysgraphia, dyscalculia or both. Results showed no statistically significant gender differences between the clinical and control groups except for syndrome Somatic Complains for girls.